The order war - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce., 2017)
Appealing to the Black order Wizards of Recluce and a young engineer named Justine, the ruler of Sarronnyn hopes to preserve an ancient matriarchy that is threatened by the White Wizards of Fairhaven, the wielders of chaos.